Formulation of an alternative diet based on Cassava (Manihot esculenta Crantz) and Cowpea (Vigna unguiculata L.) for indigenous chicken in the family sector of Mozambique (Research, Society and Development, 2023)
With the aim of producing a diet for indigenous chicken based on locally available products and using simple techniques in rural areas of Mozambique, 3 mixtures of cassava (Manihot esculenta Crantz) (24.7, 15.5 and 7.8 %) and cowpea (Vigna unguiculata L.) (75.3, 84.5 and 92.2%), with different levels of crude protein - CP (17.7, 19.8 and 21.7%) designated as T1, T2 and T3, respectively. The two ingredients were obtained in single production batches from local producers, were pre-processed and mixed. Aggregation was performed using roasting technology with manual stirring at temperatures between 80 and 90°C. After the aggregation, the characterization of the diets was carried out through physical-chemical analysis, by determining the water activity (Aw), water absorption index (IAA), moisture content, ash content, protein content, lipids, carbohydrate content and pH. Data was submitted to analysis of variance (ANOVA) followed by Tukey test using the SAS software. The diets T1, T2 and T3 presented different granulometries and colors, resulting in diets with larger, medium and smaller particles with light, less light and dark color, respectively with the increasing inclusion of cowpea flour and decreasing cassava flour. The use of cassava and cowpea for the formulation of diets for hens and the manual aggregation of the particles allowed to obtain an adequate technology for small breeders, since the experimental diets present ideal physical and chemical characteristics for their stability and feeding the hens.